Food and agriculture in urbanized societies : pathways for a better future - Schneider, Sergio; Preiss, Potira V.; Marsden, Terry (Research in rural sociology and development ;, 2022)
For the first time in human history, more people inhabit urban than rural areas. Investigating the experience of hunger and malnutrition in urban spaces, Food and Agriculture in Urbanized Societies confronts the persistence of social inequalities, constant waves of economic crises and accelerating climate shifts, asking, how and to what extent food systems will recover and rebuild after the unprecedented eruption of a pandemic? An in-depth diagnosis of the state of the art of the current and dominant agri-food system, the broad and diverse collective intelligence in this edited collection proposes alternatives for change and redesign, bringing together a set of pioneering ideas and solutions to old and new problems. From environmental regeneration and the quality of food to the nutritional, political and economic perspective, the chapters culminate with the focus on developing a more integrative and systematic approach towards urban and rural areas. Inspiring innovative and sustainable practices, governance perspectives and informing public policies, Food and Agriculture in Urbanized Societies offers the most current research on urbanized agriculture to truly provide 'pathways for a better future' to foster more equitable and fair societies.